2011
DOI: 10.4028/www.scientific.net/amr.347-353.107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Coarse Woody Debris in Different-Age Natural <i>Larix gmelinii</i> Forests in Daxing’anling Mountains

Abstract: Coarse woody debris (CWD) is composed of dry wood, fallen wood and large branches, and it is an important element for structure and function in forest ecosystems. In this paper, we studied the characteristics of coarse woody debris (CWD) of natural Larix gmelinii forests with different ages in Daxing’anling Mountains. The results show that (1) the CWD volumes in near-mature, middle-age and young forests are 88.55 m3•hm-2, 52.07 m3•hm-2 and 3.96 m3•hm-2, respectively; and their biomasses are 52.96 t•hm-2, 36.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Conversely, the biomass of fallen trees in Ncf was less than that in Pinus tabulaeformis secondary forests in the Qinling Mountains [32], and Korean pine forests in the Changbai Mountains [33]. Compared with Larix gmelinii forests in the Daxing'anling Mountains, the biomass of fallen trees in Ncf was determined to be at the middle level [34]. However, the biomass of fallen trees in Acf was higher than those in coniferous forests in Guangzhou [30], artificial Castanopsis kawakamii forests and Chinese Fir forests in Sanming [31], but less than the biomass of fallen trees in mixed coniferous forests and broad-leaved forests in Guangzhou [30] (Table A2).…”
Section: Characteristics Of Biomass and Carbon Stock Of Fallen Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the biomass of fallen trees in Ncf was less than that in Pinus tabulaeformis secondary forests in the Qinling Mountains [32], and Korean pine forests in the Changbai Mountains [33]. Compared with Larix gmelinii forests in the Daxing'anling Mountains, the biomass of fallen trees in Ncf was determined to be at the middle level [34]. However, the biomass of fallen trees in Acf was higher than those in coniferous forests in Guangzhou [30], artificial Castanopsis kawakamii forests and Chinese Fir forests in Sanming [31], but less than the biomass of fallen trees in mixed coniferous forests and broad-leaved forests in Guangzhou [30] (Table A2).…”
Section: Characteristics Of Biomass and Carbon Stock Of Fallen Treesmentioning
confidence: 99%
“…These may allow the storage of a greater carbon stock of fallen trees in a forest ecosystem [2,3]. The distribution of the diameter class of fallen trees was affected by the structural composition of forest stands, site conditions and disturbance [32][33][34]. For example, Liu et al [35] reported that coarse woody debris in evergreen broadleaved forests after an ice storm in Northern Guangdong Province yielded a large diameter class of forest stands on windward slopes that facilitated the formation of a large number of fallen trees, whereas the small diameter class of forest stands on leeward slopes was affected by low temperature and frost damage [35].…”
Section: Diameter Class Distribution Of Fallen Treesmentioning
confidence: 99%